PEMBINAAN KEAGAMAAN PADA NARAPIDANA LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS II A KOTA PALEMBANG - Yuvita Sari; Abdul Karim; Zaki Faddad Syarif Zain (Jurnal Studi Agama, 2021)
This research aims to determine the process and implementation of religious guidance on women inmates in the Women's Correctional Institution class II A Palembang City. This study uses qualitative descriptive methods. This study uses several methods in the data collection: observation, interview, and documentation methods. Data analysis techniques used are data reduction, data presentation, and conclusion. The research results showed that religious guidance on female inmates in Palembang city correctional institution is carried out intensively every day and continuously, such as prayer dhuhr congregation. The methods used are situation-based coaching methods, individual treatment methods, classical treatment methods, learning and experience methods (experimental learning), and autosuggestion. Supporting factors in spiritual development are a) LPP Palembang in collaboration with institutions related to spiritual development, b) musholla facilities in blocks, c) providing prayer equipment, and d) providing learning and teaching equipment. As for the factors that hinder religious coaching: a) the background of female inmates are not the same, b) differences in sentencing period and un concurrent entry, c) the interest of female inmates following religious coaching is lacking, d) the ability of inmates in digesting materials delivered is not the same, and e) the absence of a particular curriculum.